👤

.a).Dla każdej z podanych liczb znajdź liczbę o 9 mniejszą.

-1 -5 1 3 -9 9 17



b).Odejmij liczbę -12 od każdej z podanych liczb.

7 12 0 -6 -10 -20 -35


Odpowiedź :

a)

-1 - 9 = -(1 + 9) = -10

-5 - 9 = -(5 + 9) = -14

1 - 9 = -(9 - 1) = -8

3 - 9 = -(9 - 3) = -6

-9 - 9 = -(9 + 9) = -18

9 - 9 = 0

17 - 9 = 8

b)

7 - (-12) = 7 + 12 = 19

12 - (-12) = 12 + 12 = 24

0 - (-12) = 0 + 12 = 12

-6 - (-12) = -6 + 12 = 12 - 6 = 6

-10 - (-12) = -10 + 12 = 12 - 10 = 2

-20 - (-12) = -20 + 12 = -(20 - 12) = -8

-35 - (-12) = -35 + 12 = -(35 - 12) = -23